The effects of different prior exercises on oxygen uptake kinetics and exercise tolerance in supramaximal running performance - Moilanen, Elina (2020)
Introduction. Rapid response of VO2 kinetics at the beginning of the endurance exercise has been found beneficial for the performance. In sports, prior exercises have been used to enhance the VO2 kinetics as well as the exercise tolerance of the performance, and many earlier studies have shown beneficial effects of prior high intensity exercises on these variables. In addition to the capacities of the respiratory and circulatory systems, the importance of neuromuscular capacities in endurance performance have been noticed. The aim of this study was to investigate the effects of continuous severe intensity prior exercise and intermittent prior exercise on VO2 kinetics and exercise tolerance in supramaximal running exercise compared to continuous moderate intensity prior exercise. The second aim was to investigate associations between neuromuscular abilities and endurance performance.